THE EFFECT OF COOPERATIVE LEARNING MODEL UPON READING COMPREHENSION OF ELEVEN GRADE STUDENTS OF SMA NEGERI 1 SELONG DIFFERING IN READING INTEREST LANGUAGE EDUCATION - Pahrurrozi (Al-mujahidah, 2021)
This study aimed at finding out The Effect Of Cooperative Learning Model Upon Reading Comprehension Of Eleven Grade Students Of SMA NEGERI 1 SELONG Differing In Reading Interest. This study was experiment research used post-test only control group design. This study used random sampling technique involved 84 students consisted of eight classes that had the same competence. And then all classes were given random classes to determine the experimental group and the control group. consisted of 42 students . After that groups were given the reading interest questionnaire . From the analysis of the questionnaire , 33% (21 students ) of the high reading interest and 33 % (21 students) of the low reading interest were determined from of each group as samples. Data were collected using reading test and questionnaire reading interest. The data were analyzing two- way ANOVA. The data of the students’ achievement were obtained reading comprehension. Reading comprehension data were collected through a questionnaire of reading interest. Both of reading comprehension and reading interest had been validated before being applied to the research sample. Next, the data that were obtained were analyzed by using Two-way ANAVA analysis and Tukey Test. The result of this research is as follows: (1) There was a significant difference between the achievement of the students who were taught by cooperative learning model and those who were taught by using conventional learning model . (2) There was an interaction between the usage of cooperative learning model and reading comprehension upon students’ reading interest. From the result of this research , it can be concluded that the learning model had significant effect towards the students reading comprehension. The difference of reading comprehension mentioned shows that cooperative learning model is better or effective than conventional learning model. (3)There was a significant difference between the achievement of the students who had high reading interest being taught using cooperative learning model and those who were taught being conventional learning model. (4) there was a significant difference between the achievement of the students who had low reading interest being taught using cooperative learning model and those who were being taught using conventional learning model